Role of mantle flow in Nubia‐Somalia plate divergence. Issue 2 (20th January 2015) - Stamps, D. S.; Iaffaldano, G.; Calais, E.
Abstract Present‐day continental extension along the East African Rift System (EARS) has often been attributed to diverging sublithospheric mantle flow associated with the African Superplume. This implies a degree of viscous coupling between mantle and lithosphere that remains poorly constrained. Recent advances in estimating present‐day opening rates along the EARS from geodesy offer an opportunity to address this issue with geodynamic modeling of the mantle‐lithosphere system. Here we use numerical models of the global mantle‐plates coupled system to test the role of present‐day mantle flow in Nubia‐Somalia plate divergence across the EARS. The scenario yielding the best fit to geodetic observations is one where torques associated with gradients of gravitational potential energy stored in the African highlands are resisted by weak continental faults and mantle basal drag. These results suggest that shear tractions from diverging mantle flow play a minor role in present‐day Nubia‐Somalia divergence.